Rebound behaviour of uncoordinated EMS and their impact minimisation. Issue 2 (4th February 2020) - Mahmud, Khizir; Ravishankar, Jayashri; Hossain, Jahangir
Abstract : In this paper, the impacts of uncoordinated energy management systems (EMS), with a rebound effect, on a renewable energy‐dependent microgrid are discussed and feasible solutions are presented. Two different approaches, i.e. load‐based and price‐based EMS are modelled which consider PV units, battery energy storage systems (BESS), and electric vehicles (EVs). Taking account of each component's boundary conditions, the load‐based approach intelligently charges the EV and BESS from the grid/PV during off‐peak hours, and provides a combined discharge response during peak load hours. In the price‐based approach, the charging‐discharging of BESSs and EVs from/to grid and PV depends on the time‐of‐use tariff signal. The primary objective of both models is to minimise the customers' peak electricity consumption and the saturation issues of distribution transformers. It is observed that the simultaneous response of the EMS due to the identical behaviour of load or price curves, and the rebound effect after mode switching transition create large power demand spikes. To mitigate its negative consequence, an improved locking and randomisation technique is designed and implemented. Additionally, the impact of the PV power fluctuations on the load‐support systems due to fast‐moving clouds and their consequences to the behaviour of the EMS response are investigated.